Attachment to God and Psychological Adjustment: God's Responses and Our Coping Strategies - Parenteau, Stacy C. (Journal of religion and health, 2019)
An outgrowth of research has established an association between attachment to God dimensions and psychosocial indices. There has been a dearth of studies, however, examining variables that mediate these relationships. This study examined three categories of coping strategies (emotion-focused, problem-focused, and dysfunctional) as mediators in the relationship between attachment to God dimensions and psychological adjustment. This study employed a cross-sectional design to examine the association among attachment to God dimensions, coping strategies, and psychological adjustment among 315 undergraduate students at a midsize southeastern university. Participants completed a demographic questionnaire, the Attachment to God Inventory, the Brief COPE, the Center for Epidemiologic Studies Depression Scale, and the Positive and Negative Affect Schedule. Structural equation modeling was used to examine direct and indirect effects. Analyses revealed an indirect influence of secure God attachment on positive affect via emotion-focused coping, as well as an indirect influence of secure God attachment on all three mental health indicespositive and negative affect and depressionvia dysfunctional coping. Analyses also revealed an indirect influence of avoidant God attachment on depression and both positive and negative affect via dysfunctional coping, as well as an indirect influence of ambivalent God attachment on depression and both positive and negative affect via dysfunctional coping. Although causality cannot be established, results suggest that attachment to God dimensions are associated with psychological adjustment through the use of specific coping strategies. Future research should employ longitudinal designs in order to identify temporal influences among attachment to God dimensions, coping styles, and psychological indices.